Strategic Service Analysis Pusako Hotel to Increase Occupancy Rate - Tyas, Anggi Fitrining; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2013)
The tourism industry is the fourth largest foreign exchange earner for Indonesia after oil and gas, palm oil, rubber and processed in 2011. This industry is expected to continue to grow and expand in Indonesia in line with government programs to take advantage of all the potential of tourism in Indonesia. West Sumatra, especially the Bukittinggi is one of the favorite tourist destinations in Indonesia also felt the positive effects of tourism development in Indonesia, namely the increasing number of tourists, both domestic and foreign to this city. So the demand for hotels is also on the rise. As a result, competition among hotel service providers cannot be avoided. Pusako Hotel is a 4 star resort in Bukittinggi with 23 years of experience in the hotel industry. Since 1989 Pusako Hotel is the only 4-star hotels in Bukittinggi, until in 1995 emerging competition from competitors with the same star or with the same concept. As a result of intense competition, the last two years Pusako Hotel occupancy never reaches the target set by the management. This is also due Pusako hotel cannot provide service to the customers satisfaction. The focus of this thesis is to find a solution that can help service strategy Pusako Hotel to improve the occupancy rate. Root cause analysis is needed to determine why the Hotel Pusako unable to achieve the target occupancy. Internal analysis, analysis of business situations, and analysis of quality of service needs to be done. The analysis shows that the root of the problem that caused the decrease in occupancy Pusako Hotel is the low level of customer satisfaction, on physical facilities and service responsiveness that existed at Hotel Pusako. In addition, the position of the product life cycle Pusako Hotel is currently at maturity phase. Some service strategies recommendations are proposed to respond these conditions. The resulting strategy is to renew Segmenting, Targeting and Positioning (STP) as a basis for the establishment Pusako Hotel marketing strategy. Then the marketing strategy recommendation applied to the form of the Marketing Mix.Â Keywords: tourism, hospitality industry, Bukittinggi, hotel resort, service marketing strategy.